Critical nitrogen level determination in curcuma alismatifolia gagnep - C. Inkham (2018)
We determined the critical nitrogen (N) level in fieldgrown Curcuma alismatifolia Gagnep. by applying N at a rate of 3.75, 7.5, 15, 30, and 60 g N plant-1 as urea. Plant growth and N critical levels were determined 105 d after planting (flowering stage). To establish critical N levels in plant tissue, the relationship between rhizome yield and the N concentrations in the first fully expanded leaf from the bottom of 1st order shoots as investigated. The rate of N application had a significant effect on growth, plant dry weight, leaf N concentrations, and leaf chlorophyll content. Leaf N concentrations were similar for all treatments up to 30 g N plant-1, but increased when N was applied at 60 g N plant-1. Rhizome yields increased with increasing leaf N up to about 1-1.5% N, but were relatively constant at a higher leaf N. The critical leaf N level response to 90% of the maximum yield was 1.51%. Most N concentrations in the various tissues increased with increasing N supply. The method for determining critical N levels provides an accurate description of the relationship between leaf N and rhizome yield and may be used by growers to predict the N requirement of Curcuma plants.